Surgical Decision-Making for Temporal Lobe Epilepsy: Patient Experiences of the Informed Consent Process - Dewar, Sandra R.; Pieters, Huibrie C.; Fried, Itzhak (Frontiers in Neurology, 2021)
Background: Surgical resection is frequently the recommended treatment for drug-resistant temporal lobe epilepsy (TLE), yet many factors play a role in patients’ perceptions of brain surgery that ultimately impact decision-making. The purpose of the current study was to explore how patients experienced signing informed surgical consent for TLE, in their own words. Methods and Materials: Data was drawn from in-person, semi-structured interviews of 19 adults with TLE eligible to undergo epilepsy surgery. A systematic thematic analysis was performed to code, sort and compare participant responses. The mean age of these 12 (63%) women and seven (37%) men was 37.6 years (18-68 years), with average duration of epilepsy of 13 years (2-30 years). Results: Meeting the neurosurgeon and signing the informed consent for surgery represented an important treatment milestone across a prolonged treatment trajectory. Four themes were identified: 1) Understanding the language of risk; 2) Overcoming risk; 3) Family-centered, shared decision-making, and 4) Building decisional-confidence. Conclusion: Despite living with the restrictions of chronic uncontrolled seizures, considering an elective brain procedure raised unique and complex questions. Personal beliefs and expectations influenced how the consent process was experienced. Overall, satisfaction was expressed with the information provided, despite frequent inaccurate recall of the facts. The findings support that the practice of informed consent be conceptualized as a systematic, structured process with three stages that occurs over time: namely, preparation, signing and follow-up after signing.